Exploring the determinants associated with adult mortality in Malta: A cohort study between 2014 and 2020 - Sarah Cuschieri (Elsevier, 2024)
Objective: The study set to explore the mortality causes across six years and identify potential mortality determinates at a population level in Malta. Study design and methods: A longitudinal follow-up of a Malta based cross-sectional national representative study across 6 years (2014-2020) was carried out. The study population was cross-linked to the mortality register and causes of death obtained. Population characteristics gathered during initial examination were analysed through univariant and multivariant logistic regressions. Results: A total of 66 adults, mostly male (65.15 % n = 43) died, with commonest cause being cancer (42.42 % CI95 %: 31.24-54.45) mostly due to malignant neoplasm of bronchus and lung. This was followed by cardiac pathologies including acute myocardial infarction, ischaemic cardiomyopathy, and cardiomegaly (25.76 % CI95 %: 16.67-37.51). Multivariant logistic regression analyses revealed positive associations between age (OR: 1.99 p = 0.02), history of coronary heart disease (OR: 11.78 p=<0.001), smoking for 31 years or more (OR: 8.22 p=<0.001) and presence of multimorbidity (OR: 1.32 p = 0.02). Conclusion: It is evident that occurrence of cancers is a concern in Malta, and it requires targeted action including the reduction of smoking habits. Understanding the mortality causes and the associated determining factors at a population level enable the institution of preventive actions while strengthening healthcare services to safeguard the population from premature mortality and co-morbidity.